"He Will Wipe Every Tear from Their Eyes": The Church’s Call to Native American Boarding School Truth and Healing - Ward, Katie (Lumen et Vita, 2022)
This paper argues that the Catholic Church must support and participate in Indigenous-led truth and healing efforts for the ways that the Church perpetrated abuses and trauma through Native American boarding schools. The paper begins by examining the Church’s historical role in boarding schools and the ways that Native American Catholic schools today differ from their historical predecessors. The paper then discusses the lack of apology from the institutional Church for Native American boarding schools in the United States and various movements in the Church and Church teachings that support a commitment to truth and healing. Using the example of Red Cloud Indian School, the paper concludes with a vision of what the Church’s support of boarding school truth and healing could look like and why that is essential for the Church’s mission.